Habitat Characteristic of The Long-Tail Monkeys (Macaca fascicularis) at Natural Tourism Park (NTP) Pengsong Mount, West Lombok - Ratu Mas Tara Indriani; M. Yamin; I Putu Artayasa (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2021)
Pengsong Mount Natural Tourism Park (NTP) is a habitat for long-tailed monkeys (Macaca fascicularis) in West Lombok. This study aims to determine the habitat characteristics of Macaca fascicularis in Pengsong Mount Natural Tourism Park (NTP), West Lombok. The object of this research is the long-tailed monkey (Macaca fascicularis) and all vegetation observed in the habitat of this species. Habitat characteristic data was collected using the plot method placed on an observation transect. Vegetation data taken includes vegetation at the level of seedlings, saplings, poles, and trees. Data on the physical conditions of the habitats collected included air temperature, air humidity, soil moisture, and soil pH. The data on the activity of the long-tailed monkeys studied were the daily activities of the monkeys in their habitat. The results showed that the habitat characteristics of long-tailed monkeys in Pengsong Mount Natural Tourism Park (NTP) is overgrown by 25 types of plants belonging to 15 families, has an average air temperature of 27.670C, an average air humidity of 650C, an average soil moisture of 55.67%, and the average pH of 5.2. The value of plant diversity in the Pengsong Mount Natural Tourism Park (NTP) area is 2.623 so that the value of plant diversity is classified as moderate. The value of plant evenness in the Pengsong Mount Natural Tourism Park (NTP) area is 0.815 so that the value of plant evenness is high.